Assessment of Kitchen Feasibility Based on Hygiene–Sanitation Aspects and Food Microbiological Quality at Nutrition Fulfillment Service Units (SPPG) in Kediri Regency, East Java, Indonesia - Susi Yuliandari; Dianti Ias Oktaviasari; Mohamad Anis Fahmi (Ficco Scientific Corner, 2025)
Background: Food safety is a crucial aspect in the implementation of nutrition fulfillment services. Kitchens at the Nutrition Fulfillment Service Units (Satuan Pelayanan Pemenuhan Gizi/SPPG) play an important role in providing safe, high-quality, and consumable food. This study aimed to assess kitchen feasibility based on hygienic–sanitation aspects and the microbiological quality of food at SPPG in Kediri Regency, East Java, Indonesia. Methods: This study employed a descriptive observational design with a cross-sectional approach. The study sample consisted of all SPPG operating in Kediri Regency, selected using a total sampling technique. Data were collected through direct observation using a hygienic–sanitation checklist, short interviews, and microbiological examination of ready-to-eat food, including Total Plate Count (TPC), Escherichia coli, and Salmonella sp. Data were analyzed descriptively and compared with applicable standards. Results: The average hygienic–sanitation score of SPPG kitchens was 77%, which was categorized as feasible. The lowest scoring aspect was food handlers’ hygiene, which had not yet optimally met the required standards. Microbiological analysis indicated that all food samples met food microbiological quality standards, with TPC values below the permissible limits and no contamination by E. coli or Salmonella sp. detected. Conclusion: SPPG kitchens in Kediri Regency are generally feasible based on hygienic–sanitation aspects and microbiological food quality. However, improvements in food handlers’ hygiene through continuous training and supervision are necessary to ensure food safety.